Allergic phytodermatitis due to Toxicodendron succedaneum in sub Himalayan region of North India: a clinical study - Chauhan, Meena; Rattan, Renu; Tegta, Geeta Ram; Shekhar, Chander; Dutt, Bhupender; Sharma, Rajnish (International Journal of Research in Dermatology, 2017)
Background: Phytodermatitis refers to inflammation of the skin caused by a plant. The clinical patterns of dermatitis due to plants can present as allergic phytodermatitis, photophytodermatitis, irritant contact dermatitis or in the form of mechanical injury. The commonest plant causing allergic contact dermatitis in India is Parthenium hysterophorus, followed by other plants. Phytodermatitis due to Toxicodendron succedaneum is not uncommon in sub Himalayan range of North India and it has variable clinical presentation.The aim of the study was to study and evaluate the patients of allergic contact dermatitis due to T. succedaneum. Methods: All patients having allergic contact dermatitis due to T. succedaneum from August 2015 to July 2016 were enrolled for the study. Results: Our study included 13 (76.4%) males and 4 (23.5%) females with a mean age of 32 years. 76.4% patients developed lesions within 24-48 hours after contact with plant, 17.6% after 48 hours and 5.8% developed in less than 24 hours. Most of the (88.2%) patients presented with disseminated lesions and 11.7% had localised lesions involving only hands and forearms. Urticaria (41.1% ) was the commonest finding followed by papuloplaque lesions (in 29.4% patients), further followed by erythema multiforme like lesions (in 11.7% patients) and maculopapular, vesiculobullous lesions and angiodema (in 5.8% of each patients). Patch test was positive in 16 (94.1%) cases. Majority of patients required systemic steroids to settle the dermatitis. Conclusions: Allergic contact dermatitis due to T. succedaneum is very common in this region. Although it presents with widespread clinical presentations but adequate literature was not found on this plant. This plant further requires more study to know the dermatitis caused by it.